Advanced Performance Prediction of Triple-Junction Solar Cell Structures Using MATLAB/Simulink Under Variable Conditions - Olfa Bel Hadj Brahim Kechiche; Habib Sammouda (Energies)
Raising the efficiency of triple-junction cells such as (GaInP/GaInAs/Ge) is an important goal for designing high-concentration photovoltaic systems. This purpose can be achieved by facing cell obstacles and acting on their configurations to sustain under highly concentrated sunlight and high operating temperatures. In this paper, a prediction performance study of triple-junction solar cells with four types of structures is proposed under variable conditions. The results show that the series structure is well-validated with experimental data under standard test conditions and is presented against those under variable conditions. Then, the triple-junction cells are compared and discussed in terms of photovoltaic cell open circuit voltage, photovoltaic cell electrical efficiency, fill factor, and temperature coefficients. Consequently, the results show that the cells can be separated into two categories that are useful for Low Concentration Systems and High Concentration Systems. The Low Concentration Systems present high efficiency at 20 suns. For the High Concentration Systems, the Hybrid 2 type demonstrates an optimal efficiency of 38.48% at 118 suns with a high FF (0.873) and shows a lower temperature coefficient than the series type. So, Hybrid 2 presents a good candidate for high-concentration systems with a performance better than the conventional triple-junction cells.